Green economic system as environmental protection: case study in Pt. Pertamina Geothermal Energy Indonesia / Arif Kuswanto, Budimansyah and Okta Supriyaningsih - Kuswanto, Arif; Budimansyah; Supriyaningsih, Okta (Universiti Teknologi Mara Selangor, 2023)
The realization of the environmental protection budget by PT PGE Ulubelu looks very large and will have a positive impact, but the process of developing and exploiting geothermal energy at PT. directly side by side with the community, considering that most of the geothermal energy is there. Then, does the use of renewable energy that is in line with the green economy still have a good impact on the environment or vice versa. A research question emerged, namely: (1) How is the concept of implementing a green economy at PT. Pertamina Geothermal Energy Area Ulubelu? (2) What is the form of environmental protection at PT. Pertamina Geothermal Energy Area Ulubelu? (3) How is the concept of green economy and environmental protection at PT. Pertamina Geothermal Energy Area Ulubelu in an Islamic economic perspective? This research uses qualitative research.. By using primary and secondary data the population in this study is PT. Pertamina Geothermal Energy Area Ulubelu, The sampling technique uses purposive sampling using saturated data, namely informants are selected with certain considerations and goals. Then the addition of the sample was stopped, when the data was saturated. The results of the analysis of this research study found interesting facts and opinions where significant positives were answered that the environment around the company implements a sustainable economy and environmental protection by planting trees and CSR programs. However, there are indeed doubts whether the drilling process will cause the things mentioned in question, the fact is that this is not true, the informants have explained in interviews as well as facts from related sources. The concept of green economy is very closely related to geothermal energy, so PT. PGE Ulubelu in particular as the object of this research is said to have implemented the concept of an environmentally friendly economy / green economy, besides that environmental protection is included in the green economy principle where sustainability is an important aspect for life in the future, PT . PGE Ulubelu with the existence of TJSL / Social and Environmental Responsibility and care about the preservation of biodiversity through the budget and its realization allows it to become a pioneer of environmentally friendly renewable energy companies as an alternative source of replacing fossil fuels. In Islamic economics, the emphasis on the prohibition of destroying and exploiting nature without regard to its maintenance is also stated in the Qur'an, Surat Ar-Rum (30): 41-42. In line with the above, PT. PGE Ulubelu is committed to preserving the environment so that vegetation and ecosystems are maintained through an annual budget which is reported in the form of an annual report on biodiversity conservation. PT PGE Ulubelu Area in carrying out exploration, exploitation and production of geothermal resources always tries to place environmental aspects and responsibilities by implementing a well-integrated Company Management System.